A randomised, double‐blind, placebo‐controlled, duloxetine‐referenced study of the efficacy and tolerability of vortioxetine in the acute treatment of adults with generalised anxiety disorder. Issue 1 (January 2014) - Mahableshwarkar, A. R.; Jacobsen, P. L.; Chen, Y.; Simon, J. S.
Summary Aims This study aims to evaluate the efficacy and tolerability of vortioxetine 2.5‐, 5‐ and 10‐mg once‐daily doses vs. placebo in the treatment of generalised anxiety disorder (GAD). Methods In this 8‐week, multicentre, double‐blind, placebo‐controlled, parallel‐group, phase 3 study, patients with a primary GAD diagnosis were randomised to receive placebo (n = 157), vortioxetine 2.5 mg, vortioxetine 5 mg, vortioxetine 10 mg or duloxetine 60 mg once daily (n = 156 each). The primary end‐point, mean change from baseline in Hamilton Anxiety Scale (HAM‐A) total score and key secondary end‐points for the 5‐ and 10‐mg vortioxetine doses were analysed in a prespecified sequential testing procedure (all at week 8). Sexual dysfunction was evaluated using the Arizona Sexual Experiences Scale. Results Differences from placebo in the primary efficacy end‐point were not statistically significant for the vortioxetine groups. The mean difference from placebo was significant in the duloxetine arm. For all secondary efficacy end‐points, results were similar among the vortioxetine groups and did not reach statistical significance. The vortioxetine 10‐mg group showed separation from placebo on the Hospital Anxiety and Depression anxiety subscore (nominal p = 0.036). Duloxetine 60 mg significantly improved the primary end‐point (p < 0.05 vs. placebo), validating the study. Nausea, dry mouth, diarrhoea, nasopharyngitis, headache, dizziness, somnolence, vomiting, dyspepsia, constipation and fatigue were reported in ≥ 5% of patients receiving vortioxetine. Rates of treatment‐emergent sexual dysfunction (TESD) in the vortioxetine dosing groups were similar to placebo. Conclusion In this study, vortioxetine 2.5‐, 5‐ and 10‐mg once‐daily doses showed no significant improvement in HAM‐A total scores vs. placebo. Vortioxetine was well tolerated at all doses and was not associated with TESD.